2016
DOI: 10.3747/co.23.3273
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Survival in Patients with ALK-Positive Non-small-Cell Lung Cancer: A Canadian Retrospective Study

Abstract: Background Crizotinib was the first agent approved for the treatment of anaplastic lymphoma kinase (ALK)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
2
19
1
Order By: Relevance
“…Prior work suggested that males and females have similar PFS benefit from ALKIs, whereas the data on differences in OS by sex have been conflicting. 1,6,[13][14][15][16][17][18][19] Crizotinib is known to decrease free testosterone in males; however, although our site was active in discovering this, only 60% of males began taking crizotinib at UCCC. 20 Consequently, whether all male patients were screened and/or treated for low testosterone and the consequences of such treatment remain unknown.…”
Section: Discussionmentioning
confidence: 94%
“…Prior work suggested that males and females have similar PFS benefit from ALKIs, whereas the data on differences in OS by sex have been conflicting. 1,6,[13][14][15][16][17][18][19] Crizotinib is known to decrease free testosterone in males; however, although our site was active in discovering this, only 60% of males began taking crizotinib at UCCC. 20 Consequently, whether all male patients were screened and/or treated for low testosterone and the consequences of such treatment remain unknown.…”
Section: Discussionmentioning
confidence: 94%
“…This is particularly relevant when taking into consideration that clinical trials have a stern patient selection and thus underrepresented populations might respond differently to proposed therapy. Real-world clinical practice data on the use of crizotinib have been documented for patients in Canada [16] and China [17], and recently a large series reported on several European Union countries [18]. However, the experience in the Latin American population has been scarcely discussed [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 38 publications assessed outcomes of use of an ALK inhibitor after an initial ALK inhibitor. Of the 38 publications, 25 were from clinical trials3537,4042,6179 and 13 were from observational studies 4448,50,54,57,8084. All 38 publications reported on use of a second-generation ALK inhibitor after initial crizotinib therapy; one publication of an observational study also included a population that used a second-generation ALK inhibitor after an initial second-generation ALK inhibitor (ceritinib after initial alectinib),47 and one publication of an observational study mentioned two patients who received crizotinib after alectinib 84.…”
Section: Resultsmentioning
confidence: 99%